Comparaison des performances entre NOMA et OFDM pour le réseau 5G - حسين, دبش; عبد البديع, نصيب (Université d'El Oued, 2021)
"Wireless communications Systems are the subject of study of many researches. The purpose is to obtain a good quality of transmission at high bit rates, and to release the users from wires and cables in order to allow them to move freely in urban areas. In this type of communications system, the effect of multipath channels must be adequately combated. This has led to the development and use of the OFDM modulation technique which appears to be a very promising solution.The robustness against the spreading delay generated by a multipath channel and the high throughput are among the most interesting properties of this type of transmission. Non-orthogonal multiple access (NOMA) is a potential multiple access technique for Fifth Generation (5G) wireless networks, which has recently been proposed for the 3rd Generation Long Term Evolution Partnership Projects (3GPP-LTE-A), is a promising technology to address the aforementioned challenges in networks (5G). The technique, by allowing multiple users to share the same blocks of time and frequency by dividing their power levels. NOMA offers a set of desirable advantages, including improved spectrum efficiency, over existing orthogonal multiple access (OMA). In this thesis we first give an overview of the principle of OMA in uplink and downlink and deal with the performance in terms of capacity of this technique and the main access techniques related to this concept (Time, Frequency, Space ) with its advantages, so we will highlight a series of disadvantages that should be resolved for the OMA. Then we provide the basic principles of the NOMA technique for the downlink and uplink channels, as well as the performance of this technique. The main NOMA systems will be examined by dividing them into two categories namely the NOMA of the power domain and the NOMA of the code domain, this work mainly focuses on the NOMA in the power domain which uses overlay coding (SC) at the transmitter and successive interference cancellation (SIC) at the receiver. Finally, the results of the simulation show the throughput of NOMA versus OMA " "الشبكات اللاسلكیة ھي الھدف الذي انصبت علیھا دراسات الباحثین في الوقت الحالي،من اجل الوصول إلى جودة عالیة فينقل المعلومات و الاتصال،بأكبرسرعة واكبرتدفق مقارنة بالشبكات السلكیة لاسیما في المناطق العمرانیة. في هذا النوع من أنظمة الاتصالات ، يجب مكافحة تأثير القنوات متعددة المسارات بشكل مناسب. وقد أدى ذلك إلى تطوير واستخدام تقنية التشكيل OFDM التي تبدو حلاً واعدًا للغاية. تعد القوة ضد تأخير الانتشار الناتج عن قناة متعددة المسارات والإنتاجية العالية من بين أكثر الخصائص إثارة للاهتمام لهذا النوع من الإرسال. يعد الوصول المتعدد غير المتعامد (NOMA) هو تقنية وصول متعددة محتملة بالنسبة للشبكات اللاسلكية من الجيل الخامس (5G) ، والتي تم اقتراحها مؤخرًا لمشاريع شراكة التطور طويل الأمد للجيل الثالث (3GPP-LTE-A) ، هي تقنية واعدة لمواجهة التحديات المذكورة أعلاه في الشبكات (5G). هذه التقنية ، من خلال السماح لعدة مستخدمين بمشاركة نفس كتل الوقت والتردد عن طريق قسمة مستويات طاقتهم. تقدم NOMA مجموعة من المزايا المرغوبة ، بما في ذلك تحسين كفاءة الطيف ، على الوصول المتعدد المتعامد الحالي (OMA). في هذه الرسالة ، نقدم أولاً نظرة عامة على مبدأ OMA في الوصلة الصاعدة والهابطة والتعامل مع الأداء من حيث سعة هذه التقنية وتقنيات الوصول الرئيسية المتعلقة بهذا المفهوم (الوقت ، التردد ، الفضاء) مع مزاياها ، لذلك سنسلط الضوء على سلسلة من العيوب التي يجب حلها لـ OMA. ثم نقدم المبادئ الأساسية لتقنية NOMA لقنوات الوصلة الهابطة والوصلة الصاعدة ، بالإضافة إلى أداء هذه التقنية. سيتم فحص أنظمة NOMA الرئيسية من خلال تقسيمها إلى فئتين هما NOMA لمجال الطاقة و NOMA لمجال الكود ، ويركز هذا العمل بشكل أساسي على NOMA في مجال الطاقة الذي يستخدم تشفير التراكب (SC) في المرسل و إلغاء التداخل المتتالي (SIC) عند المستقبل. وأخيرا نتائج المحاكاة إظهار إنتاجية NOMA مقابل OMA "
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: multi-path channel, OFDM modulation, NOMA, OMA, 5G, SIC, SC.; قناة متعددة المسارات ، تعديل OFDM ، NOMA ، OMA ، 5G ، SIC ، SC.